Complex Networks and their Applications. - Cherifi, Hocine (Newcastle upon Tyne : Cambridge Scholars Publishing, 2014)
Fuelled by the big data paradigm, the study of networks is an interdisciplinary field that is growing at the interface of many branches of science including mathematics, physics, computer science, biology, economics and the social sciences. This book, written by experts from the Network Science community, covers a wide range of theoretical and practical advances in this highly active field, highlighting the strong interconnections between works in different disciplines. The eleven chapters ta ...
TABLE OF CONTENTS; PREFACE; CHAPTER ONE; CHAPTER TWO; CHAPTER THREE; CHAPTER FOUR; CHAPTER FIVE; CHAPTER SIX; CHAPTER SEVEN; CHAPTER EIGHT; CHAPTER NINE; CHAPTER TEN; CHAPTER ELEVEN; CONTRIBUTORSGiuliano
Print version record.
Includes bibliographical references.
English.
Keywords: Social networks -- Research; System analysis; Mathematics & science; Combinatorics & graph theory; Computer science; SCIENCE -- System Theory; TECHNOLOGY & ENGINEERING -- Operations Research; Social networks -- Research; System analysis; Electronic books; Electronic books